Tax law and the transfer of start-up losses: A European overview and categorization - Anna Theresa Bührle; Christoph Spengel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Most of the European Member States employ anti-loss trafficking rules. They aim to prevent the acquisition of mere corporate shells with high tax loss carryforwards for the tax asset to be utilized in profitable companies. However, other corporations can unintentionally be affected by the anti-abuse regulations if there is a change in ownership or activity. The transfer restrictions have been argued to impair start-up financing, as investors are faced with the risk of losing accumulated loss carryforwards in the corporation upon the entering of new or the capital increase of existing investors. This study provides an overview over the design and development of loss transfer restrictions in the EU28 over a time period of 19 years (2000-2018). Different aspects of the regulations are analyzed against the background of their impact on start-ups. Finally, the rules are categorized with respect to their strictness. Over time, more countries introduced restrictions. At the same time, the regulations became more lenient, offering start-ups more opportunities to maintain their loss carryforwards and, therefore, decreasing the risk for investors.
Keywords: M13; H25; H32; L52; 330; tax loss carryforward; loss trafficking; loss transfer; entrepreneurship; start-ups